2019
DOI: 10.3390/w11122639
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Micropollutants by UV–Chlorine Treatment in Reclaimed Water: pH Effects, Formation of Disinfectant Byproducts, and Toxicity Assay

Abstract: The utilization of reclaimed water is a reliable and sustainable approach to enhance water supply in water-deficient cities. However, the presence of micro-organic pollutants (MPs) in reclaimed water has potential adverse effects on aquatic ecosystems and human health. In this study, we investigated the occurrence of 12 target MPs in the influent and reclaimed water collected from a local wastewater treatment plant, and the ultraviolet (UV)-chlorine process was applied to analyze its ability to remove MPs. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 39 publications
0
18
0
2
Order By: Relevance
“…At present, the research of membrane treatment is mainly focused on optimizing the process and developing the combined process of membrane treatment and other processes (Fan, Luo, et al, 2019;Li, Zhang, Zeng, et al, 2019;Li, Zhang, Xia, Wang, et al, 2019;Li, Zhang, Hu, et al, 2019;Li, Sun, Zhang, Feng, et al, 2019;Li, Yuan, Gao, et al, 2019). Wang, Ying, Ma, Huo, and Yang (2019), Wang, Su, et al (2019), , Wang, Huang, Chan, and Zhang (2019), Wang, Cai, et al (2019), , Wang, Yin, Zeng, and Zhu (2019g), Wang, Qian, et al (2019), reported a microporous membrane, which was doped with microporous β-cyclodextrin polymer, for the removal of bisphenol A by flow-through process. The results showed that the removal rate of bisphenol A can reach more than 99.9% at the water flux of 300 L m −2 hr −1 and feed concentration of 50 mg/L.…”
Section: Membrane Processesmentioning
confidence: 99%
See 4 more Smart Citations
“…At present, the research of membrane treatment is mainly focused on optimizing the process and developing the combined process of membrane treatment and other processes (Fan, Luo, et al, 2019;Li, Zhang, Zeng, et al, 2019;Li, Zhang, Xia, Wang, et al, 2019;Li, Zhang, Hu, et al, 2019;Li, Sun, Zhang, Feng, et al, 2019;Li, Yuan, Gao, et al, 2019). Wang, Ying, Ma, Huo, and Yang (2019), Wang, Su, et al (2019), , Wang, Huang, Chan, and Zhang (2019), Wang, Cai, et al (2019), , Wang, Yin, Zeng, and Zhu (2019g), Wang, Qian, et al (2019), reported a microporous membrane, which was doped with microporous β-cyclodextrin polymer, for the removal of bisphenol A by flow-through process. The results showed that the removal rate of bisphenol A can reach more than 99.9% at the water flux of 300 L m −2 hr −1 and feed concentration of 50 mg/L.…”
Section: Membrane Processesmentioning
confidence: 99%
“…Under the optimal conditions, the maximum adsorption capacities of MAPC for imipramine and amoxicillin were 59.8 and 7.7 mg/L, respectively, which was 332% and 681% higher than that of natural clay, respectively. Wang, Ying, et al (2019), Wang, Su, et al (2019), , , Wang, Cai, et al (2019), , Wang, Yin, et al (2019), Wang, Qian, et al (2019), ) synthesized a magnetic adsorbent derived from Broussonetia papyrifera leaves (MA-BPL). Then, they used MA-BPL to adsorb methylene blue in water.…”
Section: Annual Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations